IDENTIFIKASI BERBAGAI PERMASALAHAN YANG DIHADAPI OLEH UKM DAN PENINJAUAN KEMBALI REGULASI UKM SEBAGAI LANGKAH AWAL REVITALISASI UKM - Hapsari, Ira Maya (PERMANA, 2014)
Movement of SME sector so important to create growth and jobs opportunity. SMEs is quite flexible and can easily adapt to the tides and the direction of the market demand. They also create jobs opportunity faster than other sectors, and they are also quite diversified and provide an important contribution in the export and trade. Therefore SMEs is an important aspect in the development of a competitive economy. The existence of a wide variety of definitions of SMEs in the determination of the above brings strategic consequences. Definition of a consensus on the SME entities as the basis of policy formulation that will be taken, so that at least, there are two clear definition of SMEs, namely the first, two settings for administrative purposes; and second, the goal for coachingKeywords: SMEs, regulation, revitalization